Dual-motor Synchronous Wiper System Controller Based on CAN Bus - YAN Da; WANG Xu-dong; SUN Yan-cheng (Journal of Harbin University of Science and Technology)
Single-motor wiper system through a mechanical connection to swing synchronously is widely used. This structure has the disadvantages such as large space occupation，inconvenient maintenance and so on. Dual- motor wiper system overcomes all these problems and reduces the system weight and mechanical noise，but reasonable solution of synchronous operation should be adopted. To solve this problem，this design adopted dual- motor synchronous control wiper system based on CAN( Controller Area Network) bus. The circuit of the controller was built and the reference trajectories of wiper arms were established according to the constraints of the swing process while the actual trajectory was drawn through fitting the collected position information. Based on the CAN bus，the dual-motor synchronous control was realized through master-slave synchronous control method. The results of experiments show that: dual-motor wiper system controller based on CAN bus could achieve synchronous operation of the wiper arms tracking those reference trajectories.